Accounting Standardization in the Municipality of Elvas: stages and challenges - Ventura, Ricardo (2023)
The biggest change of paradigm in the accounting system of the Portuguese public sector, take place in 1997 with the public sector reform, which materialized through the Public Official Accounting Plan. However, despite the important role played by this accounting standard, it could not keep up with international standards or the evolution of accounting in the private sector. These facts along with the multiplicity of accounting systems in the public sector and the strong need for international accounting harmonization, led, in 2015, to the approval of the Public Sector Accounting Standardization System. Thus, the emergence of new challenges in public management was the lever for the most recent reform of public accounting in Portugal operationalized by the Public Sector Accounting Standardization System and the Budgetary Framework Law. This applies to all central, regional, and local government institutions. Among local government institutions, municipalities are the most representative. Their transition from the Official Accounting Plan for Local Authorities to Public Sector Accounting Standardization System was expected to be a long and complex process mainly due to obstacles such as the adaptation of computer systems and the high number of procedures needed. Thus, this study analyzes the conceptual basis and describes the transition stages from the Official Accounting Plan for Local Authorities to Public Sector Accounting Standardization System in a Portuguese municipality. This work follows a qualitative methodology. The case study identified three critical factors for the successful implementation of the Public Sector Accounting Standardization System: human resources with experience and adequate training, adequate information systems, and institutional support from official public entities. This paper contributes to a proper application of the system through theoretical and practical explanation of the processes, at the accounting and technologies levels. By highlighting crucial points in a process of change, this paper also contributes to the success of changing processes in the public sector.